Media and Political Relations in Framing Analysis of the News of the Rejection of Rohingya Refugees in Aceh - Sulaiman, Azman; Sazali, Hasan; Nurdin, Hanifah; Putri, Nanda (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
The purpose of this research is to find out how the relationship between media and politics in the news of the rejection of Rohingya refugees in Aceh. At first the people of Aceh openly accepted Rohingya refugees to land in Aceh but in 2023 there was a rejection in a number of Acehnese waters against Rohingya refugees caused by various misleading information received by the people of Aceh. The method used is qualitative with a descriptive approach. The results showed that the mass media often used negative framing and formed negative public opinion towards Rohingya refugees, the media should be objective in presenting news, but the public must also be critical in responding to information spread in the media.